2015
DOI: 10.1007/s00455-015-9607-4
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Sensor-Guided Enteral Access Systems: A Literature Review

Abstract: Enteral feeding is the nutritional support of choice for acutely ill patients with functional gastrointestinal tracts who are unable to swallow. Several benefits including reduced mortality and length of hospital stay have been associated with early initiation of enteral feeding. However, misplacement of conventional nasoenteric tubes is relatively common and can result in complications including pneumothorax. In addition, the need to confirm the position by X-ray can delay the start of using the tube. Elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 35 publications
3
30
2
2
Order By: Relevance
“…Of the 194 patients in this study, only 1 had data showing discrepancies between the original EMPD verification and the final abdominal radiograph interpretation, providing a 99.5% agreement 26 . Other recent studies and a literature review demonstrated similar conclusions, 27 , 28 while 2 more recent papers point out the potential risk of eliminating x‐ray confirmation with inexperienced operators 29 , 30 …”
Section: Section 4 Enteral Accesssupporting
confidence: 51%
“…Of the 194 patients in this study, only 1 had data showing discrepancies between the original EMPD verification and the final abdominal radiograph interpretation, providing a 99.5% agreement 26 . Other recent studies and a literature review demonstrated similar conclusions, 27 , 28 while 2 more recent papers point out the potential risk of eliminating x‐ray confirmation with inexperienced operators 29 , 30 …”
Section: Section 4 Enteral Accesssupporting
confidence: 51%
“…There is no published case series on the utilization of EMS‐EAS in patients with heart failure with implanted cardiac devices. A review of the literature shows that there is a 43%–95% success rate of achieving postpyloric placement using EMS‐EAS in a variety of patient populations without implanted cardiac devices . Our success rate of 69% postpyloric placement in this case series is comparable with success rates of studies completed in non‐LVAD patient populations.…”
Section: Discussionsupporting
confidence: 61%
“…Risks of tube misplacement include pneumothorax, vocal cord injury (nasogastric tube syndrome), bronchopleural fistula, aspiration pneumonia, perforation of the membranous trachea or pleural parenchyma, hydrothorax, mediastinitis atelectasis, plural effusions, and death. 7 Inadvertent insertion of enteral FTs into the tracheopulmonary system during placement is not predictable from clinical signs and auscultation in highrisk patients with the following associated factors: altered mental status, preexisting endotracheal tube, critical illness, older adults, and abdominal distention. 8 In the high-risk patient, alternatives to blind FT insertion are needed to improve patient safety.…”
Section: Introductionmentioning
confidence: 99%